Impact of maternal weight on the intra‐observer and inter‐observer reproducibility of fetal ultrasonography measurements in the third trimester. Issue 1 (31st October 2017) - Policiano, Catarina; Mendes, Jorge M.; Fonseca, Andreia; Barros, Joana; Martins, Diana; Reis, Inês; Clode, Nuno; Graça, Luís M.
Abstract: Objective: To evaluate the effect of maternal weight on the intra‐ and inter‐observer reproducibility of third‐trimester ultrasonography fetal measurements. Methods: The present prospective study, performed at a tertiary hospital, enrolled patients at between 35 +0 weeks and 36 +6 weeks of singleton pregnancies between January 1, 2015, and July 1, 2016. Fetal ultrasonography measurements were evaluated twice by a first observer and a third time by a second observer. Intra‐ and inter‐observer consistency were analyzed using the Cronbach α reliability coefficient, and measurement reproducibility was compared with patients stratified by a body mass index (BMI, calculated as weight in kilograms divided by the square of height in meters) of below 25 or at least 25. Results: The study included 197 patients (133 with BMI <25 and 64 with BMI ≥25). Among patients with a BMI below 25, the reliability coefficients for bi‐parietal diameter, head circumference, abdominal circumference, and femur length measurements were 0.97, 0.95, 0.98, and 0.96, respectively, for intra‐observer consistency, and were 0.97, 0.93, 0.98, and 0.95, respectively, for inter‐observer consistency. Among patients with a BMI of at least 25, these values were 0.97, 0.96, 0.98, and 0.97, respectively, for intra‐observed consistency, and 0.97, 0.94, 0.98, and 0.96, respectively, for inter‐observer consistency. Conclusion: High intra‐ and inter‐observer reproducibility was observed for third‐trimester fetal ultrasonography measurements, including for patients who were overweight. Abstract : High intra‐ and inter‐observer reproducibility was observed for third‐trimester fetal ultrasonography measurements in pregnant patients, including those who were overweight.